Nutritional Evaluation and Risk Assessment of the Exposure to Essential and Toxic Elements in Dogs and Cats through the Consumption of Pelleted Dry Food: How Important Is the Quality of the Feed? - Ana Macías-Montes; Manuel Zumbado; Octavio P. Luzardo; Ángel Rodríguez-Hernández; Andrea Acosta-Dacal; Cristian Rial-Berriel; Luis D. Boada; Luis Alberto Henríquez-Hernández (Toxics, 2021)
Dry feed for pets lacks specific legislation regarding maximum residue limits for inorganic elements. The aim of the present study was to determine the content of 43 inorganic elements in dog and cat feed, studying whether there were differences according to the supposed quality of the food and performing the risk assessment for health. Thirty-one and thirty packages of pelleted dry food for cats and dogs, respectively, were analyzed. After acidic microwave-assisted digestion, elements were detected and quantified by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). In general, we did not observe important differences in the content of elements according to the supposed quality of the brand. Among trace elements, selenium and manganese are above the dietary reference value. Arsenic and mercury showed the highest acute hazard indexes, which make them risk factors for the health of dogs and cats. Aluminum, uranium, antimony and vanadium contents were above the toxic reference value and showed the highest acute hazard indexes. It is necessary to improve the legislation regarding the food safety of pets, for their health and to protect the rights of consumers.